The Effect Of Advertising, Product Innovation, Word Of Mouth And Social Media Role Towards Brand Awareness Of Converse Shoes In Students - Salsabila Nayanda Worabay; Putra Wisnu Agung; Dewi Pujiani; Slamet Djauhari; Ambyah Atas Aji (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2018)
In this study the author has the aim of knowing the influence of advertising, product innovation, word of mouth and the role of social media on brand awareness of converse shoes in UNSA students. The hypothesis in this study are: Allegedly advertising, product innovation, word of mouth and the role of social media have a significant effect on brand awareness of converse shoes in UNSA students. The data needed in this study are primary data obtained by questionnaire method from a sample of 100 respondents and secondary data obtained from literature. The data analysis used in this study is the classic assumption test, multiple linear regression test, t test, F test, and Determination Coefficient Test. The results of data analysis in this study can be concluded that advertising, product innovation, word of mouth and the role of social media have a significant effect on brand awareness of converse shoes in UNSA students.